Assessing health-related quality of life in schizophrenia patients using EQ-5D-5L index: Insights from patients and caregivers - A. Prasetiyo, Nugraha; Wahyudin, Elly; Setiawan, Iman; Sanusi, Mayamariska; Purba, Fredrick D.; Arifin, Bustanul; Alkaff, Sylmina D. (Narra J, 2025)
Schizophrenia is a prevalent mental health disorder often marked by relapses, significantly affecting the health-related quality of life (HRQoL) of both patients and their families. The aim of this study was to compare the EuroQol 5-Dimension 5-level (EQ-5D-5L) responses of schizophrenia patients and their caregivers. Using an observational cross-sectional design, HRQoL was assessed among schizophrenia patients and their family caregivers recruited from a provincial referral hospital. Sociodemographic (age, sex, education, marital status, income) and clinical variables (diagnosis, treatment duration, comorbidities) were analyzed alongside HRQoL using structured interviews, medical record reviews, and the EQ-5D-5L instrument (self-report by patients and proxy-reported by family caregivers). Statistical analyses included chi-square tests for associations, Wilcoxon tests for patient-family caregiver comparisons, and multivariate modeling of HRQoL determinants. A total of 526 participants (263 patients and 263 accompanying family caregivers) were included. Significant differences were observed between patients and family caregivers in two domains: pain/discomfort and anxiety/depression. Also, the agreement between patients' and family caregivers’ reports showed good results. A substantial agreement was observed between patient-reported and family caregiver-assessed HRQoL, as indicated by a Cohen’s Kappa value of 0.8. This result suggests a strong level of consistency between the two assessments, supporting the potential use of family caregivers as reliable proxies for evaluating patient HRQoL when self-reports are unavailable or unreliable. In the self-care domain, mobility, and daily activities, patient and caregiver assessments show high agreement. In conclusion, the closeness between patients and caregivers significantly influences patients' HRQoL, providing critical insights for evaluating treatment effectiveness in schizophrenia cases. While discrepancies exist between patient and caregiver assessments, these interactions are particularly impactful in subjective domains like pain/discomfort and anxiety/depression, but not for other domains that are visible.